Encyclopedia of heavy metal music - Phillips, William, 1961-; Cogan, Brian, 1967- (Westport, Conn. ; London : Greenwood, 2009)
Providing an extensive overview of the music, fashion, films, and philosophies behind the movement, this encyclopedia chronicles the history and development of heavy metal, including sub-movements such as death metal, speed metal, grindcore, and hair metal.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Heavy metal (Music) -- Bio-bibliography -- Dictionaries; Heavy metal (Music) -- Encyclopedias; Electronic books; Electronic books